PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN CANVA DALAM PEMBELAJARAN KETERAMPILAN MENULIS TEKS DESKRIPSI KELAS VII SMP PGRI 4 CIMAHI - Delina Meilani; Teti Sobari; Via Nugraha (IKIP Siliwangi, 2026)
This research is underpinned by the challenges that seventh-grade students at SMP PGRI 4 Cimahi faced in descriptive text writing skills. These were identified as deriving from the conventional learning approaches embraced by educators and the lack of innovation in utilizing instructional media. Therefore, the present research explores the viability of the PBL model, supported by media using Canva, for the enhancement of descriptive text writing skillsThe current study utilized a mixed-methods strategy, focusing on the Sequential Exploratory design.The research subjects involved 35 seventh-grade students.The data were generated through the administration of a pretest and a posttest to measure the ability to write a descriptive textThe findings reflect the improvement in the students' creative writing skills. This improvement was showcased by the increase in the mean test score from 70 in the pretest to 83.42 in the posttest. The T-test achieved a significance level of 0.000 (< 0.05). This highlights that the Alternative Hypothesis is accepted. Furthermore, N-Gain was found to be 0.56, indicating